Development of SNAP markers based on nucleotide variability of WRKY genes in coconut and their validation using multiplex PCR - ANNEKE PESIK; DARDA EFENDI; HENGKY NOVARIANTO; DINY DINARTI; SUDARSONO SUDARSONO (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Pesik A, EfendiD, NovariantoH, DinartiD, Sudarsono S. 2017. Development of SNAP markers based on nucleotide variability of WRKY genes in coconut and their validation using multiplex PCR. Biodiversitas 18: 465-475. Development of molecular markers benefits coconut breeding program. The availability of DNA sequences for coconuts opens the new possibility of developing molecular markers such as single nucleotide amplified polymorphism (SNAP). The study aimed to evaluate nucleotide sequence diversities of WRKY gene in the GenBank database, design gene specific primers for generating WRKY gene specific SNAP markers, optimize multiplex PCR technique and validate SNAP marker effectiveness for evaluating Kopyor coconut germplasm. Based on 35 sequences data of coconut WRKY genes that are available in the GenBank database, we have identified eight informative SNPs and used them to generate SNP-specific primers. We have designed sixteen primer pairs and validated them using singleplex PCR. Subsequently, we optimized the Ta and primer concentrations either for duplex or triplex PCR. Duplex PCR using two sets of primer pairs was more reliable for genotyping Kopyor coconut germplasm than triplex PCR. We have successfully demonstrated the duplex PCR for genotyping Banten Tall, Jember Tall, Kalianda Tall, Pati Dwarf and Sumenep Tall Kopyor coconuts. Therefore, one may use the developed SNAP markers as a simple alternative of co-dominant markers for genetic analysis of coconuts. One may use the developed SNAP markers to investigate the possible association between markers and Kopyor endosperm and other relevant phenotypes in coconuts.Keywords: Kopyor coconut, multiplex PCR, SNP